2003
DOI: 10.1242/dev.00315
|View full text |Cite
|
Sign up to set email alerts
|

Orbit/Mast, the CLASP orthologue ofDrosophila, is required for asymmetric stem cell and cystocyte divisions and development of the polarised microtubule network that interconnects oocyte and nurse cells during oogenesis

Abstract: Drosophila oocyte differentiation is preceded by the formation of a polarised 16-cell cyst from a single progenitor stem cell as a result of four rounds of asymmetric mitosis followed by incomplete cytokinesis. We show that the Orbit/Mast microtubule-associated protein is required at several stages in the formation of such polarised 16-cell cysts. In wild-type cysts, the Orbit/Mast protein not only associates with the mitotic spindle and its poles, but also with the central spindle (spindle remnant), ring cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 50 publications
(56 reference statements)
5
34
1
Order By: Relevance
“…The same kind of dynein dependence was described for mammalian CLIP-170 (Dujardin et al, 1998;Tanenbaum et al, 2006). It was observed that in addition to dynein, CLIP-190 also binds Mast (Mathe et al, 2003). Since CLASPs are CLIP-associated-proteins that bind to CLIP-170 through its conserved C-terminal domain (the same domain that targets Mast to kinetochores) (Akhmanova et al, 2001), it was proposed that CLIP-170 might be a linker for dynein cargo (Dujardin et al, 1998).…”
Section: Discussionsupporting
confidence: 55%
“…The same kind of dynein dependence was described for mammalian CLIP-170 (Dujardin et al, 1998;Tanenbaum et al, 2006). It was observed that in addition to dynein, CLIP-190 also binds Mast (Mathe et al, 2003). Since CLASPs are CLIP-associated-proteins that bind to CLIP-170 through its conserved C-terminal domain (the same domain that targets Mast to kinetochores) (Akhmanova et al, 2001), it was proposed that CLIP-170 might be a linker for dynein cargo (Dujardin et al, 1998).…”
Section: Discussionsupporting
confidence: 55%
“…We note that the ring canal phenotype seen in kelch mutants is remarkably specific: the loss-of-function ovarian germline phenotypes of thousands of genes-perhaps a third of the genome-have been examined (see Hudson and Cooley 2014 for review of systematic genetic screens performed in the ovary), and yet only four genes are known to result in a kelchlike phenotype. Two of these are kelch and Cul3, while in the other two, Impa2 and orbit, the phenotypes appear to result from a failure to localize Kelch to ring canals (Gorjanacz et al 2002;Mathe et al 2003). Thus to our knowledge, all characterized mutations that result in a kelch-like phenotype are required for Kelch function in some manner.…”
Section: Kelch Functions As An E3 Ubiquitin Ligase In Vivomentioning
confidence: 93%
“…CLASPs are required to maintain a stem cell component in Drosophila and for ordered cell migration in vertebrates (Mathe et al 2003;Lee et al 2004) and can be critically important for localized modulation of microtubule dynamics (Inoue et al 2004). Mammalian CLASPs stabilize the association of microtubules and the cell cortex (Mimori-Kiyosue et al 2005).…”
mentioning
confidence: 99%